2010
DOI: 10.1097/wad.0b013e3181c53b00
|View full text |Cite
|
Sign up to set email alerts
|

A Single Ascending Dose Study of Bapineuzumab in Patients With Alzheimer Disease

Abstract: The safety, tolerability, and pharmacokinetics (PKs) of bapineuzumab (AAB–001), a humanized monoclonal antibody to amyloid β, were evaluated in patients with mild-to-moderate Alzheimer disease in a phase 1, randomized, third-party unblinded, placebo-controlled, single ascending dose trial. Thirty patients received bapineuzumab infusion of 0.5, 1.5, or 5mg/kg or placebo (6 active, 2 placebo for 0.5 and 1.5-mg/kg cohorts; 10 active, 4 placebo for 5.0-mg/kg cohort). Three patients in the highest dose cohort (5.0m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
123
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 15 publications
6
123
2
Order By: Relevance
“…1,5 This constellation of imaging features is in keeping with the hypothesis of altered vascular permeability, 6,8 which is now recognized as part of the ARIA spectrum. ARIA-E specifically refers to associated parenchymal edema and sulcal effusions, whereas ARIA-H refers to hemosiderin deposits from blood products within the parenchyma or leptomeninges.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…1,5 This constellation of imaging features is in keeping with the hypothesis of altered vascular permeability, 6,8 which is now recognized as part of the ARIA spectrum. ARIA-E specifically refers to associated parenchymal edema and sulcal effusions, whereas ARIA-H refers to hemosiderin deposits from blood products within the parenchyma or leptomeninges.…”
Section: Discussionmentioning
confidence: 73%
“…Imaging findings reported with bapineuzumab have occurred in both phase 1 and 2 clinical studies and have typically been identified in asymptomatic patients undergoing routine scheduled MR imaging surveillance. 1,5 These MR imaging findings were characteristic of transiently extravasated fluid within the brain parenchyma and were initially described as vasogenic edema among AD clinical specialists. 5 With time, a more diverse set of imaging changes was noted that could not be accurately described by the term "vasogenic edema."…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that vascular dysfunction may be the first 'hit' in a 'two-hit' process that leads to AD, 12 in which the second hit is the abnormal accumulation of Ab. Because immunotherapy approaches to AD have shown adverse effects consistent with breakdown of BBB (such as a redistribution of amyloid from parenchyma to vasculature and increased microhemorrhage in mouse models, [56][57][58] as well as inflammation, vasogenic edema, and microhemorrhage in some AD patients, 59,60 ) it has been proposed 61 that Ab may have a protective role and may normally act to stabilize the BBB. In our studies, however, improved cerebral perfusion and vascular density were associated with decreased plaque deposition as well as with decreases in CAA and reduced microhemorrhage, which are not consistent with expected outcomes of chronic BBB destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are also naturally observed in AD, because lobar microbleeds are related to cerebral amyloid angiopathy and AD pathology. 5,10,[11][12][13][14][15] Because both findings are considered related to amyloid pathology, the term "amyloid-related imaging abnormalities" has been proposed. ARIA is further subdivided into ARIA-H, representing hemosiderin deposits or superficial hemosiderosis, and ARIA-E, representing parenchymal vasogenic edema or sulcal effusion.…”
mentioning
confidence: 99%